Consensus Guidelines for Improving Quality of Assessment and Training for Neuromuscular Diseases - Duong, Tina; Krosschell, Kristin J.; James, Meredith K.; Nelson, Leslie; Alfano, Lindsay N.; Eichinger, Katy; Mazzone, Elena; Rose, Kristy; Lowes, Linda P.; Mayhew, Anna; Florence, Julaine; King, Wendy; et al. (Frontiers in Genetics, 2021)
Critical components of successful evaluation of clinical outcome assessments (COAs) in multisite clinical trials and clinical practice are standardized training, administration and documented reliability of scoring. Experiences of evaluators, alongside patient differences from regional standards of care, may contribute to heterogeneity in clinical center’s expertise. Achieving low variability and high reliability of COA is fundamental to clinical research and to give confidence in our ability to draw rational, interpretable conclusions from the data collected. The objective of this manuscript is to provide a framework to guide the learning process for COAs for use in clinics and clinical trials to maximize reliability and validity of COAs in neuromuscular disease (NMD). This is a consensus-based guideline with contributions from fourteen leading experts in clinical outcomes and the field of clinical outcome training in NMD. This framework should guide reliable and valid assessments in NMD specialty clinics and clinical trials. This consensus aims to expedite study start up with a progressive training pathway ranging from research naïve to highly experienced clinical evaluators. This document includes recommendations for education guidelines and roles and responsibilities of key stakeholders in COA assessment and implementation to ensure quality and consistency of outcome administration across different settings.